Socioeconomic and psychosocial factors influence pain or physical function in Asian patients with knee or hip osteoarthritis. Issue 11 (1st November 2002) - Thumboo, J; Chew, L-H; Lewin-Koh, S-C
Abstract : Objective: To determine factors influencing pain or physical function in Asian patients with osteoarthritis (OA). Methods: 126 consecutive Chinese (110), Malays (two), Indians (10), or other races (four) with knee or hip OA and a median age of 60.5 years were seen at a tertiary referral centre; 103 were women. Subjects underwent a structured assessment including the Short Form-36 (SF-36) bodily pain (BP) and physical functioning (PF) scales and assessing demographic, socioeconomic, psychosocial, and other characteristics. Factors influencing BP or PF were identified using separate multiple linear regression models. Results: The index joint (that is, the most symptomatic joint) was the knee in 118 (94%) and the hip in eight (6%) patients. The median duration of pain and limitation of normal activities were three years and one year, respectively. The mean BP and PF scores of 57.7 and 56.2 points for the patients were substantially lower than the expected scores of 79.3 and 80.8 points for the general Singapore population. Multiple regression analysis showed that less pain was associated with a younger age, shorter duration of symptoms, more years of education, working, and Chinese ethnicity. Better physical function was associated with more years of education, less learned helplessness, less bodily pain, and less severe OA. Conclusions: Socioeconomic status and psychosocial factors, some of which are potentially modifiable, influence pain or physical function in Asian patients with OA in Singapore.